D'Souza, Victor G. (Hrsg.), In the Service of Truth and Justice. Festschrift in Honour of Prof. Augustine Mendoça, Bangalore 2008: [Rezension] - Gonzales, Javier (Philippine canonical forum, 2009)
Festschrift für Prof. Augustine Mendoça.